Androgen Receptor Signaling Positively Regulates Monocytic Development - Consiglio, Camila Rosat; Gollnick, Sandra O. (Frontiers in Immunology, 2020)
Myeloid cells are critical cells involved in the orchestration of innate and adaptive immune responses. Most myeloid cells derive from the adult bone marrow in a process called myelopoiesis, a tightly controlled process that ensures constant production of myeloid cells. Sex differences in myeloid cell development have been observed; males exhibit greater monocytic differentiation in the bone marrow and men having increased blood monocyte numbers when compared to women. Here we use a genetic mouse model of myeloid androgen receptor (AR) knockout (MARKO) and pharmacological inhibition of AR to investigate the role of androgen signaling in monocytic differentiation. We observe that although myeloid AR signaling does not influence total bone marrow cell numbers, it does affect the composition of the bone marrow myeloid population in both homeostatic and emergency settings. Genetic deletion of AR in myeloid cells led to reduced monocytic development in vivo. Similarly, pharmacologic inhibition of AR signaling in vitro reduced monocytic development. However, alteration in monocytic differentiation in the absence of AR signaling did not lead to reduced numbers of circulating myeloid cells, although MARKO male mice display reduced ratio of classical to non-classical monocytes in the blood, implying that blood monocyte subsets are skewed upon myeloid AR deletion. Our results suggest that the sex differences observed in monocytic differentiation are partly attributed to the positive role of the androgen-AR axis in regulating monocytic development directly at the myeloid cell level. Furthermore, we have identified a novel role for AR in regulating blood mature monocyte subset turnover. Investigating how androgen signaling affects monocytic development and monocyte subset heterogeneity will advance our understanding of sex differences in monocytic function at homeostasis and disease, and can ultimately impact future therapeutic design targeting monocytes in the clinic.